Análisis vertical de los estados financieros de la Cooperativa de Ahorro y Crédito “San Antonio” Ltda. Los Ríos en los periodos 2021 – 2022. - Jordán Elizondo, Jennifer Lisbeth (2024)
As far as knowledge is concerned, it is conceptualized that the analysis of financial statements is a fundamental tool or main piece in any business or company, whether it is large, medium or small, regardless of the type of activity it is carrying out or develops. The evaluation or analysis of financial results over time allows comparisons to be made to the values obtained and is of great help to identify trends, strengths or weaknesses in the financial situation of companies. A due or correct follow-up and sufficient control of the financial situation allows to implement in time the correct and efficient measures necessary to implement action plans, thus allowing sustainability over time, which is the objective of any company or business in the commercial or market environment. By using vertical analysis, it is possible to identify which accounts or records constitute a greater or lesser part of the total income or expenses, thus being particularly useful to detect deviations or anomalies in the financial statements. As part of the development of this research, the calculation and interpretation of the financial indicators corresponding to it is made known with the only objective of obtaining a better vision or possible precision of the panorama of the real situation of the company.